2023
DOI: 10.1080/10717544.2022.2162158
|View full text |Cite
|
Sign up to set email alerts
|

Development of phospholipon®90H complex nanocarrier with enhanced oral bioavailability and anti-inflammatory potential of genistein

Abstract: Genistein (GEN), an isoflavonoid, offers multifunctional biological activities. However, its poor oral bioavailability, aqueous solubility, extensive metabolism, and short half-life restricted its clinical use. Therefore, the Phospholipon ® 90H complex of genistein (GPLC) was prepared to enhance its biopharmaceutical properties and anti-inflammatory activity. GPLC was characterized by employing particle size and zeta potential, Fourier transforms infrared spectrophotometry, differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…[18]. This interaction promotes the integration of the SM molecule into the polar head of the phospholipid, while the hydrophobic tail portion of the phospholipid ensures the proper orientation of this complex, leading to the formation of an amphiphilic complex that enhances transportation from an aqueous environment to a lipid-soluble environment [45]. Following the formation of the PC, the constituents' membrane permeability and oil-water partition coe cient would experience a substantial increase.…”
Section: Resultsmentioning
confidence: 99%
“…[18]. This interaction promotes the integration of the SM molecule into the polar head of the phospholipid, while the hydrophobic tail portion of the phospholipid ensures the proper orientation of this complex, leading to the formation of an amphiphilic complex that enhances transportation from an aqueous environment to a lipid-soluble environment [45]. Following the formation of the PC, the constituents' membrane permeability and oil-water partition coe cient would experience a substantial increase.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies related to shortages in outpatient pharmacy were reported. [7][8][9][10][11] This essay can be used as a reference to highlight all the various factors that should be considered while formulating a definition that will be used throughout the EU. 3…”
Section: Discussionmentioning
confidence: 99%
“…142−145 For example, phospholipon 90H complex of genistein not only improved the water solubility, dissolution rate, membrane permeation rate, and oral bioavailability of genistein but also significantly enhanced its anti-inflammatory activity. 146 Notably, Fe 2 O 3 /Fe 3 O 4 @mSiO 2 nanoparticles of apigenin had good magnetic targeting and showed stronger antitumor activity by promoting ferroptosis in A549 cells. 147 In addition, the existing research on flavonoids targeting ferroptosis mainly focuses on animal experiments and in vitro cell experiments, so there is still a lack of scientific evidence to support their clinical application.…”
Section: Future Perspectivementioning
confidence: 97%
“…As an excellent natural product, flavonoids are beneficial to human health and have few adverse side effects. , It is important to recognize that the bioavailability of most dietary flavonoids is low, which is related to factors such as structure, glycosylation, and colonic microbial metabolism . Structural modification and novel delivery systems are common methods to improve the bioavailability and efficacy of flavonoids. For example, phospholipon 90H complex of genistein not only improved the water solubility, dissolution rate, membrane permeation rate, and oral bioavailability of genistein but also significantly enhanced its anti-inflammatory activity . Notably, Fe 2 O 3 /Fe 3 O 4 @mSiO 2 nanoparticles of apigenin had good magnetic targeting and showed stronger antitumor activity by promoting ferroptosis in A549 cells .…”
Section: Future Perspectivementioning
confidence: 99%